高速干式飞刀铣齿切削温度仿真分析及实验研究 - 林超; 周鹏举; 丘华 (Jixie chuandong)
According to the knowledge of Heat Transfer and Metal Cutting Theory, high-speed dry gear milling by flying cutter to simulate the gear hobbing process is adopted. The milling temperature model of milling by flying cutter is established based on metal cutting and diathermanous theory. The multiple-factor cutting temperature calculation formulas are derived out, and combined with the flying cutter high-speed dry cutting experiment, then it is contrasted the experimental data to the theoretical data, the relationship and the changing rule among main cutting parameter is studied. The exactness of the theoretical simulation model is verified. The foundation is established for further studying the cutting temperature of high-speed dry gear hobbing and its’ cutting mechanism.